Umayamnon Tribes’ Awareness on their Right to Education: Basis for Intervention - Comonong, Ken L.; Ellorda, Jesseil Mae L.; Babasol, Robeliza G.; Ally, Glades S. (Universitas Muhammadiyah Yogyakarta, 2023)
The Umayamnon tribe in Sitio Calacapan, Cabanglasan, Bukidnon shows signs that this tribal community is insecure about essential government services, especially education. These issues are visible in the Umayamnon Tribe in Sitio Calacapan, Philippines, where these tribal groups do not have equal access to primary Education. The purpose of this study is to improve the awareness of this tribal group on their rights to Education and to make this paper the basis of the Government's provision of educational establishments and facilities in the tribal community. This study used a Descriptive-quantitative research design to assess their awareness regarding their rights to Education accurately and applied purposive sampling. A survey form was employed to gather data. The findings state that the participants have 'fair awareness' of their right to Education as mandated in the IPRA Law 1997. Further, it was found that the Umayamnon Tribes' level of awareness showed a significant difference when the participants were grouped according to their highest level of educational attainment. Therefore, The Umayamnon Tribe in Sitio Calacapan is not well informed or knowledgeable of their rights and privileges as members of the IPs/ICCs vis-à-vis their Right to Education, and the Participants’ level of Education influences their awareness of their right to Education. Further, this is an alarming message to the National Department of Education (DepEd), the National Commission on Indigenous People (NCIP), Indigenous People Mandatory Representatives (IMPRs), and the Local Government Units (LGUs) of the Philippines to further boost and provide more mechanisms for addressing this issue.